2020
DOI: 10.1371/journal.pone.0238318
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing hemodynamic response alterations during basketball dribbling

Abstract: Knowledge on neural processing during complex non-stationary motion sequences of sportspecific movements still remains elusive. Hence, we aimed at investigating hemodynamic response alterations during a basketball slalom dribbling task (BSDT) using multi-distance functional near-infrared spectroscopy (fNIRS) in 23 participants (12 females). Additionally, we quantified how the brain adapts its processing as a function of altered hand use (dominant right hand (DH) vs. non-dominant left hand (NDH) vs. alternating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…The fact that there was no significant hemispheric difference in activation in the NDH group, reflects the comparably high spread of activation in the LH and the RH, meaning that there was no significant shift in activation towards the RH in the NDH group. It was shown in previous studies, that higher complexity of a motor task [ 32 , 57 59 ] results in higher bilateral cortical activation intensity. Carius et al [ 32 ] showed that different levels of task complexity of a basketball dribbling task induce altering hemodynamic response patterns, and that a higher level of perceived difficulty is associated with higher hemodynamic response in ipsilateral sensorimotor regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that there was no significant hemispheric difference in activation in the NDH group, reflects the comparably high spread of activation in the LH and the RH, meaning that there was no significant shift in activation towards the RH in the NDH group. It was shown in previous studies, that higher complexity of a motor task [ 32 , 57 59 ] results in higher bilateral cortical activation intensity. Carius et al [ 32 ] showed that different levels of task complexity of a basketball dribbling task induce altering hemodynamic response patterns, and that a higher level of perceived difficulty is associated with higher hemodynamic response in ipsilateral sensorimotor regions.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown in previous studies, that higher complexity of a motor task [ 32 , 57 59 ] results in higher bilateral cortical activation intensity. Carius et al [ 32 ] showed that different levels of task complexity of a basketball dribbling task induce altering hemodynamic response patterns, and that a higher level of perceived difficulty is associated with higher hemodynamic response in ipsilateral sensorimotor regions. The results of Verstynen et al [ 57 ] and Haaland et al [ 58 ] reveal that ipsilateral SMC activation during left-hand movement is stronger during the execution of a more complex motor task, relative to a more simple motor task and Alahmadi et al [ 59 ] found that higher complexity of a hand-gripping task resulted in stronger involvement of the left hemisphere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hemodynamic response function (HRF) was modeled using a consecutive sequence of Gaussian functions, each with a standard deviation of 1.0 s and temporally spaced 1.0 s apart, as done by Yücel 32 . For each source-detector pair, the influence of systemic physiology and extracerebral contaminations from superficial layers were mitigated by performing short separation regression (SSR) 32 using as a regressor the data from the most correlated short channel 33 . The beta values (weight of regressors) were obtained using ordinary least squares fit.…”
Section: Methodsmentioning
confidence: 99%
“…For each source-detector pair, the influence of systemic physiology and extracerebral contaminations from superficial layers were mitigated by performing short separation regression (SSR) 32 using as a regressor the data from the most correlated short channel 33 . The beta values (weight of regressors) were obtained using ordinary least squares fit.…”
Section: Fnirs Channel Selection and Data Extractionmentioning
confidence: 99%